A Communicative Constitutive Perspective on Corporate Social Responsibility: Ventriloquism, Undecidability, and Surprisability. Issue 1 (January 2020) - Cooren, François
Adopting a communication as constitutive of organization (CCO) perspective on ethics and corporate social responsibility (CSR) invites us to create the conditions of a dialogue, discussion, or debate between various stakeholders, who can then try to confront their respective positions on a given issue, and possibly come to a decision regarding how a situation should be evaluated and/or responded to. As shown in this article, getting human stakeholders to voice their concerns about a specific situation is a way not only to rationally confront multiple viewpoints on what should be done about it (à la Habermas) but also to allow elements of this situation to reveal themselves in a discussion. This is why any ethical decision has to experience a form of undecidability and surprisability . When beliefs and opinions can be called into question, it means that participants are ready to become attentive to what a situation might surprisingly call for. Communication is therefore a matter of ventriloquism, as human participants should also be considered the means by which elements of a situation manage to express themselves in a discussion, dictating specific courses of action over others. This concretely means that multiple voices can be heard in such a scene: not only the voices of the human stakeholders who speak to each other but also the voices of facts, principles, future generations, ecosystems, populations that are made to say things through these various turns of talk.